Digital Competence of Young Adults in Poland - Małgorzata Ćwiek; Katarzyna Maj-Serwatka (Acta Universitatis Lodziensis. Folia Oeconomica)
Digital transformation is a challenge for many areas of modern society functioning. The effects of digitalisation are particularly noticeable in the labour market and are expressed, among others, in new requirements of employers both for professionally active people and those entering the labour market. Technological advances and automation are reducing the number of low skilled jobs. Moreover, employees are required to be more flexible. As a consequence, there is a need to adapt to changing trends in the labour market, and to constantly learn and acquire new competences, including digital competences.